Optimizing Firewall Log File Classification with Multilayer Perceptrons - Rojarath, Artitayaporn; Srisaengchan, Nantanee; Jabjone, Saisunee; Tipprasert, Suda; Surinta, Olarik (Engineering Access, 2026)
Cyber threats remain a major concern for network security and data integrity, often causing serious consequences through unauthorized access, data breaches, and malware attacks. Intrusion detection systems are essential for countering these risks by continuously monitoring and classifying network activities. This study investigates the use of multilayer perceptrons (MLPs) to optimize firewall log file classification and improve the identification of network events. Four activation functions (Linear, Sigmoid, Tanh, and ReLU) were examined to determine the optimal configuration. The MLP model consistently achieved high performance, with accuracy exceeding 99%, and the ReLU activation function demonstrated superior effectiveness. The synthetic minority oversampling technique was applied to handle class imbalance in the firewall log dataset, improving the detection accuracy of the minority reset-both class. Moreover, feature selection using XGBoost reduced the input set from eleven to five key attributes, achieving 99.84% accuracy and improving computational efficiency. Experimental evaluations confirmed that the proposed model effectively recognizes complex nonlinear relationships in network data. These results demonstrate the potential of MLPs to enhance the accuracy, efficiency, and robustness of firewall log file classification for modern intrusion detection systems